1997
DOI: 10.1021/es9609415
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Lifetimes of Peroxynitrates Occurring in the Atmospheric Degradation of Oxygenated Fuel Additives

Abstract: Peroxynitrates are thermally unstable intermediates in the atmospheric degradation of hydrocarbons. New classes of peroxynitrates, alkoxyalkyl and alkoxyformyl peroxynitrates, can be formed during the atmospheric degradation of dialkyl ethers being extensively used as fuel additives. In this paper, the thermal lifetimes of methoxymethyl peroxynitrate, methoxyformyl peroxynitrate, and tertbutoxyformyl peroxynitrate [i.e., RO 2 NO 2 with R ) CH 3 OCH 2 , CH 3 OC(O), and t-C 4 H 9 OC(O), respectively] are reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 18 publications
(25 reference statements)
2
34
0
Order By: Relevance
“…2.2.3. After the UV lamp is turned off, the ratio between PAN and PANs inside the chamber is fixed since the thermal lifetimes of both species are very similar (Kirchner et al, 1997(Kirchner et al, , 1999 and wall losses are negligible. This ratio was determined by FTIR and checked during the course of the experiment, and the stability of the mixing ratios inside the chamber was confirmed.…”
Section: Dissociation Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…2.2.3. After the UV lamp is turned off, the ratio between PAN and PANs inside the chamber is fixed since the thermal lifetimes of both species are very similar (Kirchner et al, 1997(Kirchner et al, , 1999 and wall losses are negligible. This ratio was determined by FTIR and checked during the course of the experiment, and the stability of the mixing ratios inside the chamber was confirmed.…”
Section: Dissociation Temperaturementioning
confidence: 99%
“…(Tyndall et al, 2004;Wallington et al, 2001;Kirchner et al, 1997). Methyl formate is used primarily in the chemical industry to manufacture formamide, dimethylformamide and formic acid.…”
Section: Mass 75mentioning
confidence: 99%
See 1 more Smart Citation
“…Vehicle exhaust emissions data have shown that acetaldehyde emissions can increase by as much as 100% with the use of 2.0 wt % ethanol oxygenated gasoline, part of which undergoes photochemical reactions in the atmosphere to make peroxyacetyl nitrate (PAN) (17). Reuter et al (4) reported that benzene emissions are reduced by fuel oxygenate.…”
Section: Figure 3 Effect Of Ethanol Concentration and Vehicles' Emismentioning
confidence: 99%
“…XO 2 accounts for additional NO to NO 2 conversions, MO 2 represents methyl peroxy radical and ACO 3 regroups all the acetyl peroxy and higher saturated acyl peroxy radicals. Further details can be found in Atkinson (1994), Kirchner et al (1997) and V2003.…”
Section: Numerical Setupmentioning
confidence: 99%